Hindu-Christian Dialogue: Perspectives and Encounters - Thottakara, Augustine (Journal of Dharma, 1992)
Harold Coward (ed.), Hindu-Christian Dialogue, Perspectives and Encounters, (Faith Meets Faith Series), New York: Orbis Books, 1 990, pp. xxi+281 .